2020
DOI: 10.3389/fnbeh.2020.00122
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine and Acetylsalicylic Acid Inhibit Alcohol Consumption by Different Mechanisms: Combined Protection

Abstract: Chronic ethanol intake results in brain oxidative stress and neuroinflammation, which have been postulated to perpetuate alcohol intake and to induce alcohol relapse. The present study assessed the mechanisms involved in the inhibition of: (i) oxidative stress; (ii) neuroinflammation; and (iii) ethanol intake that follow the administration of the antioxidant N-acetylcysteine (NAC) and the anti-inflammatory acetylsalicylic acid (ASA) to animals that had consumed ethanol chronically. At doses used clinically, NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 78 publications
(128 reference statements)
0
30
0
Order By: Relevance
“…Interestingly, the activation of mGluR2/3 by NAC also restores the NAcc ability to recover neuronal synaptic adaptations. Consequently, the antagonists of mGluR2/3 prevent the rescuing effect of cocaine-seeking behavior and relapse to ethanol consumption by NAC [144,147,148].…”
Section: Drugs Of Abuse Modify the Extracellular Levels Of Glutamatementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the activation of mGluR2/3 by NAC also restores the NAcc ability to recover neuronal synaptic adaptations. Consequently, the antagonists of mGluR2/3 prevent the rescuing effect of cocaine-seeking behavior and relapse to ethanol consumption by NAC [144,147,148].…”
Section: Drugs Of Abuse Modify the Extracellular Levels Of Glutamatementioning
confidence: 99%
“…Interestingly, aspirin treatment promotes additional anti-inflammatory mechanisms compared to other NSAIDs, as COX2 acetylated by aspirin can metabolize arachidonic acid to induce the generation of aspirin-induced lipoxins, with potent anti-inflammatory activity [191]. Recently, lipoxin administration was found to significantly inhibit chronic ethanol intake in rats and the administration of a lipoxin antagonist prevented the effect of aspirin in reducing ethanol intake [148], again showing a clear association between dug intake and inflammation.…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 99%
“…These results, together, support a crucial role of the TRPM2 channel in mediating EtOH-induced microglial cell death. It is known that exposure to alcohol leads to oxidative stress and activation of PARP [ 8 , 9 , 10 ] and, as introduced earlier, PARP activation is the major signaling mechanism for oxidative stress-induced TRPM2 channel activation, including in microglial cells [ 25 , 26 , 27 , 28 , 29 , 31 , 32 , 33 ]. As described in our recent study examining cell death induced by ROS or Zn 2+ in primary microglial cells [ 25 ], and in this study showing H 2 O 2 -induced cell death in BV2 microglial cells ( Figure 2 e–h), EtOH-induced microglial cell death was remarkably attenuated by treatment with PJ34 and DPQ, two structurally different PARP inhibitors ( Figure 3 ), supporting that PARP activation is critical in EtOH-induced TRPM2-mediated microglial cell death.…”
Section: Discussionmentioning
confidence: 99%
“…ROS production is one of the common events involved in mediating TRPM2 channel activation [ 26 , 27 , 28 , 29 ]. It has been well documented that EtOH can stimulate ROS production [ 9 ] via induction of NOX [ 11 ]. Consistent with this notion, we showed that exposure to high concentrations of EtOH induced a significant increase in ROS production in microglial cells ( Figure 4 a,b) and, furthermore, that EtOH-induced microglial cell death was prevented by treatment with PKC and NOX inhibitors ( Figure 4 c–f), consistent with the notion that PKC/NOX-mediated ROS production acts as an upstream mechanism in mediating EtOH-induced TRPM2 channel activation and microglial cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation